INWIGILACJA I INFILTRACJA JAKO EFEKTYWNE METODY UZYSKIWANIA INFORMACJI OPERACYJNYCH NA TEMAT ŚRODOWISKA PRZESTĘPCZEGO LUB KRYMINOGENNEGO - Teluk, Rafał (Zeszyty Prawnicze, 2016)
INVIGILATION AND INFILTRATION: EFFECTIVE METHODS FOR THE COLLECTION OF INFORMATION ON A CRIMINAL OR CRIMINOGENIC ENVIRONMENT Summary This article is an attempt to give a systematic presentation of the Polish police’s use of invigilation and infiltration of a criminal and/or criminogenic environment as operational and investigative methods to obtain information. The author presents the definitions of the concept of operational and investigative activities (czynności operacyjnorozpoznawcze) as put forward by the theoreticians, and discusses the methods it employs. He also defines the aims of the extra-judicial operations carried out by the authorised state entities, giving the legal grounds and principles governing operational tactics. He discusses the legalisation of documents used by police officers carrying out operations and persons assisting the police and prosecuting authorities. Another issue discussed are the ways in which information obtained from a criminal and/or criminogenic environment by means of invigilation and infiltration is used in criminal proceedings.